Palynological evidence for the Neogene environment analysis of the Thakkhola Graben, Nepal (Journal of Nepal Geological Society, 2020)
The Thakkhola Graben, a north-south graben, lies in central Nepal Himalayas consisting of Neogene sediments. The presence of pollens in these sediments provides a unique natural laboratory to understand the paleoenvironment during the formation of the graben. This study provides a detailed description of the pollen collected from the Tetang and Thakkhola formations with the help of the Light Microscope and Scanning Electron Microscope. A variety of pollen assemblages from the Thakkhola Graben explains that the sediments contain dominant alpine trees with some steppe vegetation. Presence of evergreen subtropical and temperate deciduous broad-leaved forest, needle-leaved element, and high altitude taxa show a mixed pollen assemblage in fluvial-lacustrine sediments of the graben. The presence of evergreen subtropical and temperate deciduous broadleaf forest (Quercus, Betula, Juglans, Alnus), needle-leaved element (Pinus, Tsuga) and high altitude taxa (Picea, Abies) with Artemisia, Chenopodiaceae, Poaceae, Rosaceae show mixed pollen assemblages indicating warm and humid paleoclimate. The coniferous pollen indicates the altitude was higher during the deposition time and the presence of Betula, Quercus, and Juglans suggests temperate forest. Domination of Artemisia and Chenopodiaceae shows a strong influence of the Himalayan topographic barrier during the sediment deposition.